Testing Death Penalty Opinions With General Questions and A Specific Case Scenario: Potential Lessons From China - Liang, Bin (International journal of offender therapy and comparative criminology, 2024)
Despite rich literature on public opinion on capital punishment, only a few studies examined people’s death penalty support within specific contexts. None have explored if correlates that influence people’s opinion would hold the same effect in general questions and specific case scenarios. Similarly, the Marshall hypotheses have not been tested with specific crime scenarios. Based on a sample of 1,077 students in a quasiexperimental design, this study contrasts Chinese students’ death penalty opinion in general questions with a specific crime scenario, and tests the Marshall hypotheses with the latter. Compared to their support in general questions, students’ support for death sentences dropped significantly in the specific crime scenario. Multivariate analyses showed that different factors influenced people’s decisions in the general questions and in the specific case, and respondents’ choices of preferred punishment in the specific crime scenario failed to lend support to the Marshall hypotheses.